The Urgency of Non-Formal Education Curriculum for Marginal Women - Mahfuzi Irwan; Heny Vrisca (Journal of Millennial Community, 2022)
This article aims to discuss the importance of the non-formal education curriculum for marginalized women in living their lives. This article was written through a review of scientific literature such as articles from reputable journals and other sources that have been validated by the author. The results of the study show that the non-formal education curriculum is very important for marginalized women to assist in the achievement of the Women's Life Skills Education (PKH-P) program. With the program curriculum, marginalized women are able to help themselves to be more empowered and get out of their marginal conditions for a better life.